The Use of Placebo and Non-Specific Therapies and Their Relation to Basic Professional Attitudes and the Use of Complementary Therapies among German Physicians – A Cross-Sectional Survey - Linde, Klaus (Public Library of Science, 2014)
We aimed to investigate the use of placebos (e.g. saline injections) and non-specific treatments (e.g. vitamin supplements in individuals without a relevant deficiency) among physicians working in private practices in Germany, and how such use is associated with the belief in and the use of complementary and alternative treatments, and basic professional attitudes. A four-page questionnaire was sent to nationwide random samples of general practitioners (GP), internists and orthopaedists working in private practices. The response rate was 46% (935 of 2018). 24% of GPs, 44% of internists and 57% of orthopaedists had neither used pure placebos nor non-specific therapies in the previous 12 months. 11% percent of GPs, 12% of internists and 7% of orthopaedists had exclusively used pure placebos; 30%, 33% and 26%, respectively, had exclusively used non-specific therapies; 35%, 12% and 9% had used both. Age, sex and agreement to the statement that physicians should harness placebo effects were not significantly associated with any pattern of use. Exclusive use of pure placebos was associated with being a GP, being an internist, and having unorthodox professional views. In addition to these three factors, a lower use of CAM therapies and a wish for having more time was associated with the exclusive use of non-specific therapies. Among physicians using both pure placebo and non-specific therapies, heterodox views were also somewhat more pronounced. However, associations were particularly strong for being a GP (Odds ratio 11.6 (95%CI 6.41; 21.3)) and having orthodox views (Odds ratio 0.10 (95%CI 0.06; 0.18)) among this group. In conclusion, the use of placebos and non-specific treatments varies strongly between medical specialties and is associated with basic professional attitudes. The findings support the view that the use of placebos and, in particular, of non-specific therapies is primarily a coping behaviour for difficult and uncertain situations.